2021
DOI: 10.7150/thno.55672
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence in hepatocellular carcinoma induced by a long non-coding RNA-encoded peptide PINT87aa by blocking FOXM1-mediated PHB2

Abstract: Rationale: Recently, long non-coding RNAs (lncRNAs), known to be involved in human cancer progression, have been shown to encode peptides with biological functions, but the role of lncRNA-encoded peptides in cellular senescence is largely unexplored. We previously reported the tumor-suppressive role of PINT87aa, a peptide encoded by the long intergenic non-protein coding RNA, p53 induced transcript ( LINC-PINT). Here, we investigated PINT87aa's role in hepatocellular carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 36 publications
2
43
0
1
Order By: Relevance
“…Recent advances in bioinformatics and biochemical methodologies have revealed that lncRNAs may harbor concealed peptides or proteins; however, only a few have been functionally veri ed and characterized [16], and fewer articles reported lncRNA-encoded proteins/peptides function in cancer progression (8-9) [29]. Here, we have identi ed and characterized the functions of a conserved protein encoded by the lncRNA HCP5 during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in bioinformatics and biochemical methodologies have revealed that lncRNAs may harbor concealed peptides or proteins; however, only a few have been functionally veri ed and characterized [16], and fewer articles reported lncRNA-encoded proteins/peptides function in cancer progression (8-9) [29]. Here, we have identi ed and characterized the functions of a conserved protein encoded by the lncRNA HCP5 during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This study proved for the first time that the lncRNA encoded by the nuclear genome might act as a new epigenetic player and regulate mitochondrial metabolism through mitophagy. In a second study, Xiang et al (2021) observed the overexpression of PINT87, a peptide encoded by p53-induced transcript LINC-PINT, in senescent HCC cells. Overexpression of PINT87 inhibited mitophagy by directly binding to FOXM1 and blocking the transcription of PHB2, a crucial IMM receptor for Parkin-induced mitophagy.…”
Section: Lncrnas Emerge As New Epigenetic Regulators Of Mitophagy In Cancersmentioning
confidence: 93%
“…This study proved for the first time that the lncRNA encoded by the nuclear genome might act as a new epigenetic player and regulate mitochondrial metabolism through mitophagy. In a second study, Xiang et al (2021)…”
Section: Lncrnas Are New Epigenetic Players In Mitophagymentioning
confidence: 94%
“…Subsequent studies found that lncRNA LINC-PINT can encode an 87-aa small peptide named PINT87aa to perform biological functions. PINT87aa can induces cell cycle arrest and cell senescence by directly binding to FOXM1 to block PHB2 transcription ( 77 ).…”
Section: Lncrna Encoded Small Peptidesmentioning
confidence: 99%